IMU-based assessment of ground contact time in 100-meter sprints - Blauberger, P.; Horsch, A.; Lames, M. (spinfortec2020digital: 13. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 24.-25. September 2020 in Bayreuth, 2020)
This study describes a method for extracting ground contact time (GCT) in sprinting from IMU signals. 576 steps from 26 sprints of elite sprinters are validated with Optogait measurements. Differences of 1.2 ± 8.8ms or 4.3% are found. The results show the high potential of IMUs to provide GCTs. Sensor-based measurements of running parameters allow for detailed analysis in fast and explosive sports such as the 100-meter sprint. At present, the use of these sensors is in-creasing in commercially distributed systems. Future studies can consider combining sensory data to a more holistic acquisition of running parameters.